The Impact Of Word Of Mouth And Brand Image On Purchase Decision: Study In Wall Street English Bandung - Putri, Denissa Aulia; Saputri, Marheni Eka (eProceedings of Management, 2023)
The large number of companies trying to expand their market has led to the importance of improving the quality of human resources in each region, one of which is communication. Therefore, English language skills are needed in the world of work because it is felt that it can improve one's communication skills. This research was conducted to determine the effect of word of mouth and brand image on purchasing decisions at one of the English language institutions in Bandung